The Development Strategy of Muslim Friendly Tourism in Palembang City - Anggara, Ary; Rahmanita, Myrza; Ingkadijaya, Rahmat; Nurmalinda, Elda (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2024)
After the COVID-19 pandemic, Muslim-friendly tourism has become a significant attraction in several Asian countries, including Indonesia. This study aims to analyze the potential strategies for Muslim-friendly tourism and identify effective development strategies. The methods used include descriptive qualitative analysis and SWOT analysis. Data collection techniques involved documentation, observation, and interviews with informants selected based on predetermined sampling criteria. The results indicate that the involvement of various parties in the development of Muslim-friendly tourism is focused on fulfilling their respective roles and functions, particularly in terms of regulations, policies, and the provision of halal-certified food and hotels that meet Muslim-friendly tourism standards. However, the destination lacks adequate standards to become a leading Muslim-friendly tourism destination. Keywords: Muslim-Friendly Tourism, Potential of Muslim-Friendly Tourism, Strategies for Muslim-Friendly Tourism Development, Halal Certification, Development of Muslim-Friendly Tourism Destinations